Media Pembelajaran berbasis Digital E-book pada Mata Pelajaran IPAS dan Pengaruhnya terhadap Hasil Belajar Peserta Didik - Robi’ati Fauziyah (LPPM Universitas PGRI Adi Buana, 2024)
One of the functions of learning media is as a tool in delivering material to students in learning activities. The digital learning media is one of the easy-to-apply alternative learning media and follows the evolution of the digital age. By leveraging the digital learning medium, it is expected that the learning objectives can be achieved optimally with an effective and efficient process. (Ulfah, et al, 2023). The e-book presents a new colour in the world of education, shifting the use of printed books (conventional), e-books provide convenience and convenience for anyone who wants to access the learning material anywhere and anytime. The samples in the study were students of classes IV and V in the State Department of 1 Kedungpring, Lamongan. The research methodology used is quantitative with experimental quasics. The results of the study showed that there was an influence on the use of digital e-book-based learning media on the learning outcomes of pupils. Compared to the control class that uses conventional book learning media, the experimental class has a higher average score. Kata Kunci : media pembelajaran, e-book, hasil belajar